Interventions to mitigate the risks of COVID-19 for people experiencing homelessness and their effectiveness: a systematic review - Ogbonna, Obianuju; Bull, Francesca; Spinks, Bethany; Williams, Denitza; Lewis, Ruth; Edwards, Adrian (Frontiers in Public Health, 2024)
People experiencing homelessness also experience poorer clinical outcomes of COVID-19. Various interventions were implemented for people experiencing homelessness in 2020-22 in different countries in response to varied national guidance to limit this impact of COVID-19. It is important to understand what was done and the effectiveness of such interventions. This systematic review aims to describe interventions to mitigate the risks of COVID-19 in people experiencing homelessness and their effectiveness.A protocol was developed and registered in PROSPERO. Nine databases were searched for studies on interventions to mitigate the impact of COVID-19 in people experiencing homelessness. Included studies were summarised with narrative synthesis.From 8233 references retrieved from the database searches and handsearching, 15 were included. There was a variety of interventions, including early identification of potential COVID-19 infections, provision of isolation space, healthcare support, and urgent provision of housing regardless of COVID-19 infection.The strategies identified were generally found to be effective, feasible and transferable. This review must be interpreted with caution due to the low volume of eligible studies, and low quality of the evidence available.• Wide range of renowned databases searched.• Stakeholder reports included-encompassing a range of perspectives.• Restricting the population to adults means impact of children's homelessness on clinical outcomes has not been explored in this systematic review.